ALDH1L2 drives HCC progression through TAM polarization - Jiajun Li; Chi Zhang; Qingqing Zhou; Qinqin Long; Jiayi Chen; Lili Meng; Wei Tian; Yue Yang; Chao Ge; Yuting Su; Xi-Dai Long; Jun Wu; et al. (JHEP Reports)
Background & Aims: Dysregulation of one-carbon metabolism is considered an early hallmark of mitochondrial dysfunction and cancer metabolism. ALDH1L2 belongs to the aldehyde dehydrogenase family and plays an important role in tumor progression. However, little is known about the precise role and underlying mechanisms of ALDH1L2 in hepatocellular carcinoma (HCC). Methods: Immunohistochemistry, western blotting, and immunofluorescence staining were used to evaluate ALDH1L2 expression in HCC samples (n = 90) and cell lines (n = 9). A series of in vitro and in vivo assays were performed to explore the role and molecular mechanism of ALDH1L2 in HCC progression. Results: ALDH1L2 upregulation is associated with poor prognosis in HCC (hazard ratio 1.923; 95% confidence interval 1.03–3.59; p = 0.04). ALDH1L2 promotes tumor cell proliferation and metastasis by activating NRF2/IL-6/STAT3 signaling. ALDH1L2 promotes mitochondrial respiration, increases ATP production and protects HCC cells from reactive oxygen species-induced cellular damage via NRF2 stabilization. NRF2 also directly binds to the ALDH1L2 promoter and increases ALDH1L2 transcription, thereby establishing a positive feedback loop to maintain the function of ALDH1L2. The interaction between tumor-associated macrophages and ALDH1L2-overexpressing HCC cells further promotes HCC progression. In addition, ALDH1L2 knockdown enhances the anti-HCC activity of the tyrosine kinase inhibitor sorafenib. Conclusions: These findings provide the first evidence indicating that ALDH1L2 is directly involved in tumor progression by interacting with tumor-associated macrophages through the Jak2/STAT3 signaling pathway and that ALDH1L2 may be a target molecule for HCC therapy. Impact and implications:: This research highlights that ALDH1L2 could serve as a predictive and prognostic marker in HCC. We found that a positive feedback loop between ALDH1L2 and NRF2 promotes HCC progression by activating the IL-6/Jak2/STAT3 signaling axis and tumor-associated macrophage polarization. In addition, we found that ALDH1L2 knockdown enhances the anti-HCC effect of sorafenib.